2005
DOI: 10.1002/pmic.200401284
|View full text |Cite
|
Sign up to set email alerts
|

A reference map and identification of porcine testis proteins using 2-DE and MS

Abstract: The development of the testis is essential for maturation of male mammals. A complete understanding of proteins expressed in the testis will provide biological information on many reproductive dysfunctions in males. The purposes of this study were to apply a proteomic approach to investigating protein composition and to establish a 2-D PAGE reference map for porcine testis proteins. MALDI-TOF MS was performed for protein identification. When 1 mg of total proteins was assayed by 2-D PAGE and stained with collo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 60 publications
2
24
0
Order By: Relevance
“…Reference map of proteome has been established for many bacteria, including some important pathogens [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The 2-DE proteome database focused on pathogenic bacteria has been established since 1999 [27].…”
Section: Introductionmentioning
confidence: 99%
“…Reference map of proteome has been established for many bacteria, including some important pathogens [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The 2-DE proteome database focused on pathogenic bacteria has been established since 1999 [27].…”
Section: Introductionmentioning
confidence: 99%
“…The proteomics of mammal testis should be the first effort to describe these processes and deal with testis-specific proteins to explore their structures and functions as well as their implicated clinical applications. However, fewer related works were done systematically, most of which focused mainly on the description of protein isoforms, differential protein expressions (7,8,10,11). Limitations and biases of traditional proteomics stunt functional analysis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis of spermatogenesis (7) and porcine (8), mouse (9), human testis (10,11) provided useful resources for studying of the testis developmental biology and pathology. However, most of these data were not publicly available and were not validated furtherly on gene or protein levels, and it also included many abundance proteins.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Thus far, only a few pig reproduction-associated proteomic studies using reproduction organs such as oocytes, testis, oviductal epithelium, and boar spermatozoa have been conducted. [17][18][19][20] Lee et al 21) reported that placental insufficiency in a cloned pig obtained by somatic cell-derived nuclear transfer showed high relevance to the apoptotic signaling pathway including 14-3-3 and Annexin V proteins compared to normal placenta using two-dimensional gel electrophoresis (2-DE) analysis. Although some of the mechanisms involved in reproduction have been revealed using the 2-DE approach, this method is limited due to poor sensitivity, low throughput, and low reproducibility.…”
Section: Quantitation Of Placenta Proteomes By Spectral Countingmentioning
confidence: 99%